2007
DOI: 10.1039/b707953b
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and autophagic responses to Bcl-2 inhibition and photodamage

Abstract: Among the cellular responses to photodamage initiated by photodynamic therapy (PDT) are autophagy and apoptosis. While autophagy is a reversible process that can be both a survival and a death pathway, apoptosis is irreversible, leading only to cell death. In this study, we followed the fate of mouse leukemia L1210 cells after photodamage to the endoplasmic reticulum (ER) using a porphycene photosensitizer, where Bcl-2 was among the PDT targets. In wild-type cells, we observed a rapid wave of autophagy, presum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 24 publications
(39 reference statements)
4
68
0
1
Order By: Relevance
“…Inactivation or photodamage of Bcl-2 was also reported to increase autophagy induced by PDT (10,19). However, although autophagy was enhanced when apoptosis was impaired, Kessel et al have reported that autophagy accompanied apoptosis in photosensitized leukaemia cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation or photodamage of Bcl-2 was also reported to increase autophagy induced by PDT (10,19). However, although autophagy was enhanced when apoptosis was impaired, Kessel et al have reported that autophagy accompanied apoptosis in photosensitized leukaemia cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when Bcl-2 is a principal target of photodamage after 9-capronyloxytetrakis (methoxyethyl)porphycene (CPO)-mediated PDT, the consequent loss of Bcl-2 function is proposed to stimulate autophagy, likely by disrupting its association with the proautophagic protein Beclin 1. 128 On the other hand, overexpression of Bcl-2 influences only apoptosis but not autophagic flux after PDT with silicon phtalocyanine (Pc4), 66 thus suggesting that this is not a general mechanism launching autophagy in photosensitized cells. When the ER is the main organelle damaged after PDT with hypericin, 125 the rapid shutdown of the AktmTOR pathway, which may promote a proautophagic environment, has been observed (Dewaele et al unpublished results).…”
Section: Sod Catalase and Gsh Reductase Mimeticmentioning
confidence: 99%
“…Autophagy enhances the survival of cells showing low levels of photodamage (10), thus serving as a pro-survival response by recycling damaged organelles. In contrast, autophagy induces the death of cells treated with high-dose PDT (11,12). Some studies have shown that PDT limits autophagy and apoptosis (13).…”
Section: Introductionmentioning
confidence: 99%